Reforming the public administration: the role of crisis and the power of bureaucracy - Asatryan, Zareh; Heinemann, Friedrich; Pitlik, Hans (European journal of political economy, 2017)
The need to balance austerity with growth policies has put government efficiency high on the economic policy agenda in Europe. Administrative reforms that boost the internal efficiency of bureaucracy can alleviate the trade-off between consolidation and public service provision. Against such a backdrop, this paper constructs (and makes available) a novel reform indicator to explore the determinants of public administration reforms for a panel of EU countries. The findings support political-economic reasoning: An economic and fiscal crisis is a potent catalyst for reforms, but a powerful bureaucracy constrains the opportunities of a crisis to promote reform. Furthermore, there is some suggestive evidence for horizontal learning from other EU countries, and for vertical learning associated with a particular type of EU cohesion spending.
Available online 12 August 2016
Gesehen am 14.08.2018